Need Analysis of Speaking Skill by Using Simulation for Students of Primary School Teacher Education - Dayu Retno Puspita; Asih Rosnaningsih (English Department - University of Sultan Ageng Tirtayasa, 2019)
There are several types of activities carried out to improve student speaking skills in English, one of which is simulation. Simulations of speaking skills in learning English must also be tailored to the needs of PGSD students. This study aims to find out and describe the student needs of Primary School Teacher Education in English speaking skills using simulation. Data obtained from questionnaires and interviews. The results of the analysis of learning needs obtained are that students need speaking skills fluently and communicatively in order to prepare them to meet their professional demands as an elementary school teacher later. Needs analysis data designed to reveal a) The current process of speaking English skills in the Muhammadiyah Elementary School Teacher Education Study Program, b) Student needs and difficulties in learning activities using simulation, c) Student needs and desires in speaking skills learning using simulation. Needs analysis reveals that (1) Learning activity activities needed by students are simulations (2) Student's difficulties in speaking skills in learning activities using the most dominant simulation is the lack of confidence and grammar, (3) Desired material in learning activities using simulation in the form of materials relating to elementary school material. The results of this study are expected to be a reference for preparing syllabi and developing teaching material.